Flos magnoliae constituent fargesin has an anti-allergic effect via ORAI1 channel inhibition - Hong, Phan Thi Lam; Kim, Hyun Jong; Kim, Woo Kyung; Nam, Joo Hyun (The Korean journal of physiology & pharmacology, 2021)
magnoliae (FM), the dry flower buds of or its related species, is a traditional herbal medicine commonly used in Asia for symptomatic relief of and treating allergic rhinitis, headache, and sinusitis. Although several studies have reported the effects of FM on store-operated calcium entry (SOCE) the ORAI1 channel, which is essential during intracellular calcium signaling cascade generation for T cell activation and mast cell degranulation, the effects of its isolated constituents on SOCE remain unidentified. Therefore, we investigated which of the five major constituents of 30% ethanoic FM (vanillic acid, tiliroside, eudesmin, magnolin, and fargesin) inhibit SOCE and their physiological effects on immune cells. The conventional whole-cell patch clamp results showed that fargesin, magnolin, and eudesmin significantly inhibited SOCE and thus human primary CD4 T lymphocyte proliferation, as well as allergen-induced histamine release in mast cells. Among them, fargesin demonstrated the most potent inhibitory effects not only on ORAI1 (IC = 12.46 ± 1.300 µM) but also on T-cell proliferation (by 87.74% ± 1.835%) and mast cell degranulation (by 20.11% ± 5.366%) at 100 µM. Our findings suggest that fargesin can be a promising candidate for the development of therapeutic drugs to treat allergic diseases.